Iron-nitrogen co-doped charcoal sheet as well as preparation method and application thereof
By synthesizing iron-nitrogen co-doped biochar sheets in molten salt medium, and activate persulfate by using singlet oxygen and electron transfer mechanisms, the problem of poor activation effect of biochar is solved, and efficient selective degradation of organic pollutants in the oil field production water is achieved.
Patent Information
- Application Number
- CN202410229963.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-29
- Publication Date
- 2025-08-29
AI Technical Summary
In the prior art, biochar has poor activation effect on persulfate, and cannot effectively remove organic pollutants in the oil field production water. Moreover, traditional catalysts are inefficient in complex water bodies and are easily disturbed by inorganic salts and natural organic matter.
Using nitrogen-rich sesame oil waste and ferric chloride as precursors, iron-nitrogen-co-doped two-dimensional biochar sheets are synthesized in the molten salt medium, and the persulfate is activated by using singlet oxygen and electron transfer mechanisms to form an efficient catalytic oxidation system.
Iron-nitrogen co-doped biochar flakes can quickly oxidize organic pollutants in oilfield production water, have high selectivity, and are almost unaffected by inorganic salts and natural organic matters, achieving selective degradation of target pollutants.
Smart Images

Figure CN120550840A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of oilfield produced water treatment, and in particular relates to an iron-nitrogen co-doped biochar sheet and a preparation method and application thereof. Background Art
[0002] Oilfield produced water contains a large amount of organic pollutants. Currently, the peroxymonosulfate-catalyzed oxidation process is widely regarded as an effective method to remove persistent organic pollutants in the environment. For example, Chinese invention patent application CN 107055744A discloses a method for using secondary iron minerals to activate peroxymonosulfate to generate free radicals to degrade pollutants adsorbed on the surface of secondary iron minerals and in water bodies. The water treatment method of the present invention is as follows: crushed and sieved secondary iron minerals and peroxymonosulfate are added to the water to be treated at the same time, and stirred. For another example, Chinese invention patent application CN 114229949A discloses a method for removing organic pollutants in water by light-assisted activation of peroxymonosulfate, which comprises the following steps: adding iron-doped carbon nitride material to water containing organic pollutants, adding peroxymonosulfate to carry out oxidative degradation under the assistance of visible light.
[0003] This method activates peroxymonosulfate using a catalyst or specific catalytic means to generate a variety of reactive oxygen species to decompose organic pollutants. These reactive oxygen species include sulfate radicals, hydroxyl radicals, and non-radical singlet oxygen. Although sulfate radicals and hydroxyl radicals have strong redox potentials and can rapidly degrade organic pollutants, their disadvantage is also very obvious, namely, they are not selective. Real water bodies and wastewater often contain a large amount of natural organic matter and inorganic salts. These coexisting substances will also consume a large amount of sulfate radicals and hydroxyl radicals, thereby significantly inhibiting the treatment efficiency of the oxidation system.
[0004] Therefore, non-radical activation pathways using peroxymonosulfate can effectively address this problem. Non-radical pathways include singlet oxygen, electron transfer, and high-valent metals. These non-radical pathways are highly selective and avoid interference from aqueous anions and natural organic matter, making them highly suitable for practical applications. Consequently, there is an urgent need to develop efficient, low-cost, and environmentally friendly catalysts for practical applications.
[0005] Many materials, such as graphene, carbon nanotubes, nanodiamonds, single-atom catalysts, and some metal oxides, can effectively activate peroxymonosulfate through mechanisms such as singlet oxygen or electron transfer. However, these materials often struggle to strike a balance between performance and cost, often being either too expensive or exhibiting insufficient performance, which hinders their practical application in engineering. From a practical application perspective, biochar stands out due to its unparalleled advantages in cost and yield. However, raw biochar exhibits very poor activation effects on peroxymonosulfate, preventing it from being put into practical applications. Therefore, appropriate modification methods are crucial to transitioning biochar from the laboratory to practical applications.
[0006] Co-doping with iron and nitrogen can solve the problem of poor biochar performance. For example, Chinese invention patent application CN115259336A discloses a method for improving the electron utilization rate of nano-zero-valent iron in the reduction and purification of selenite and selenate in water, comprising the following steps: (1) pyrolyzing seafood waste shells to obtain a biochar sample; (2) soaking the biochar sample in an acidic solution to decalcify, washing it to neutrality, and drying it to obtain nitrogen-doped biochar; (3) placing the nitrogen-doped biochar and iron salt in a solution of water and ethanol, adding a reducing agent solution and stirring until the reaction is complete, magnetically separating, rinsing, and drying it to obtain nitrogen-doped biochar loaded with nano-zero-valent iron; and (4) adding the nitrogen-doped biochar loaded with nano-zero-valent iron to selenium-containing wastewater. Introducing nitrogen and iron into the carbon framework of biochar can change the electronic configuration of biochar, significantly reducing its chemical inertness, and thus greatly improving its activation performance.
[0007] In addition, defects can significantly enhance the activation performance of biochar towards peroxymonosulfate. It has been demonstrated that pyrolysis of biomass in a molten salt medium can significantly increase the degree of defects in biochar. In addition, since the molten salt is in a liquid state, it can easily penetrate the carbon framework of biochar, thereby hindering the formation of van der Waals forces, inhibiting the accumulation of sp2 coordinated carbon layers, and ultimately promoting the formation of thin layer structures. Compared with 3D structures, 2D thin layer structures are beneficial for ensuring sufficient contact between biochar and the liquid medium, and these thin layer structures can also accelerate electron transfer during the catalytic process. Therefore, the molten salt strategy is a method that can improve the activation performance of biochar towards peroxymonosulfate.
[0008] In summary, addressing current shortcomings in this field, this invention uses nitrogen-rich sesame oil-pressing waste and ferric chloride as precursors to synthesize iron- and nitrogen-co-doped two-dimensional thin-layer biochar in a molten salt medium. This material exhibits exceptionally strong activation properties for peroxymonosulfate, driven by singlet oxygen and electron transfer, resulting in highly selective applications in various realistic heavy oil produced water treatment processes with complex backgrounds. Summary of the Invention
[0009] Purpose of the invention: In order to address the deficiencies of the above-mentioned prior art, the present invention provides an iron-nitrogen co-doped biochar sheet, and a preparation method and application thereof. The present invention uses nitrogen-rich sesame oil pressing waste and ferric chloride as precursors to synthesize two-dimensional iron-nitrogen co-doped biochar sheets in a molten salt medium. The iron-nitrogen co-doped biochar sheet has extremely strong oxidizing ability when combined with peroxymonosulfate, and the activation process is dominated by two non-free radical mechanisms, singlet oxygen and electron transfer, which can oxidize organic pollutants in water extremely quickly and effectively without being affected by various inorganic salts in the water. The present invention selected tetracycline as a model pollutant and found that the iron-nitrogen co-doped biochar sheet activated peroxymonosulfate can oxidize more than about 95% of tetracycline within ten minutes, and various inorganic salts have almost no effect on the degradation of tetracycline in the catalytic oxidation system.
[0010] Technical solution: The first aspect of the present invention provides an iron-nitrogen co-doped biochar sheet, which uses sesame meal and trivalent iron salt solution as precursors to synthesize two-dimensional iron-nitrogen co-doped biochar sheets in molten salt.
[0011] A second aspect of the present invention provides a method for preparing iron-nitrogen co-doped biochar flakes.
[0012] A third aspect of the present invention provides the use of the above-mentioned iron-nitrogen co-doped biochar sheets in treating organic pollutants in oilfield produced water.
[0013] The present invention has the following beneficial effects:
[0014] (1) The iron-nitrogen co-doped biochar flakes provided by the present invention have a strong activation effect on peroxymonosulfate, with performance far exceeding that of the original biochar, and the activation process of peroxymonosulfate is dominated by singlet oxygen and electron transfer;
[0015] (2) The iron-nitrogen co-doped biochar flakes and peroxymonosulfate provided by the present invention constitute a catalytic oxidation system dominated by singlet oxygen and electron transfer. The catalytic oxidation system has the ability to rapidly oxidize organic pollutants, can greatly reduce the interference of natural organic matter, inorganic salts and other substances in real water bodies on the reaction process, and can selectively degrade target pollutants. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The accompanying drawings, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0017] Figure 1a This is the SEM image of the original biochar BC-800 of Comparative Example 2.
[0018] Figure 1b This is the SEM image of the biochar SBC-800 of Comparative Example 1.
[0019] Figure 1c This is the SEM image of the iron-nitrogen co-doped biochar flakes FSBC-800 obtained in Example 1.
[0020] Figure 2a These are the XRD patterns of the iron-nitrogen co-doped biochar flakes FSBC-500, FSBC-600, FSBC-700, FSBC-800, and FSBC-900 in the present invention.
[0021] Figure 2b These are the XRD patterns of the iron-nitrogen co-doped biochar flakes FSBC-800, original biochar BC-800, and biochar SBC-800 in the present invention.
[0022] Figure 3a These are Raman spectra of the iron-nitrogen co-doped biochar flakes FSBC-500, FSBC-600, FSBC-700, FSBC-800, and FSBC-900 of the present invention.
[0023] Figure 3b These are the Raman spectra of the iron-nitrogen co-doped biochar flakes FSBC-800, original biochar BC-800, and biochar SBC-800 in the present invention.
[0024] Figure 4a These are the FTIR images of the iron-nitrogen co-doped biochar flakes FSBC-500, FSBC-600, FSBC-700, FSBC-800, and FSBC-900 of the present invention.
[0025] Figure 4b FTIR images of the iron-nitrogen co-doped biochar flakes FSBC-800, original biochar BC-800, and biochar SBC-800 in the present invention.
[0026] Figure 5 This is a schematic diagram of the activation effect of iron-nitrogen co-doped biochar flakes FSBC-500, FSBC-600, FSBC-700, FSBC-800, and FSBC-900 provided by the present invention on peroxymonosulfate.
[0027] Figure 6 Schematic diagram of the degradation effect of tetracycline on the catalytic oxidation system composed of iron-nitrogen co-doped biochar sheets and peroxymonosulfate provided by the present invention.
[0028] Figure 7 Schematic diagram of the degradation effect of tetracycline on the catalytic oxidation system composed of iron-nitrogen co-doped biochar sheets and peroxymonosulfate provided by the present invention at different catalyst concentrations.
[0029] Figure 8Schematic diagram of the degradation effect of tetracycline on the catalytic oxidation system composed of iron-nitrogen co-doped biochar sheets and peroxymonosulfate provided by the present invention at different peroxymonosulfate concentrations.
[0030] Figure 9a-9f Schematic diagram of the degradation effect of tetracycline on the catalytic oxidation system composed of iron-nitrogen co-doped biochar sheets and peroxymonosulfate provided by the present invention in the presence of different anions.
[0031] Figure 10 This is a schematic diagram of the quenching effect of ethanol, tert-butanol, furfuryl alcohol, chloroform and dimethyl sulfoxide on the catalytic oxidation system composed of iron and nitrogen co-doped biochar sheets and peroxymonosulfate provided by the present invention.
[0032] Figure 11a This is the LSV curve of iron-nitrogen co-doped biochar flakes FSBC-800.
[0033] Figure 11b This is the IT curve of iron-nitrogen co-doped biochar flakes FSBC-800.
[0034] Figure 11c This is the open circuit voltage curve of iron-nitrogen co-doped biochar sheet FSBC-800. DETAILED DESCRIPTION
[0035] The specific embodiments of the present invention are described in detail below.
[0036] The "ranges" disclosed herein are defined in terms of lower and upper limits. A given range is defined by selecting a lower limit and an upper limit, and the selected lower and upper limits define the boundaries of the particular range. Ranges defined in this manner can be inclusive or exclusive of the end values and can be combined arbitrarily, i.e., any lower limit can be combined with any upper limit to form a range. For example, if a range of 10-50 is listed for a particular parameter, it is understood that ranges of 10-40 and 20-50 are also contemplated. Furthermore, if the minimum range values listed are 1 and 2, and if the maximum range values listed are 3, 4, and 5, then the following ranges are all contemplated: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise specified, the numerical range "ab" is an abbreviation for any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed herein, and "0-5" is merely an abbreviation for these numerical combinations.
[0037] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0038] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0039] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0040] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0041] Unless otherwise specified, the reaction is carried out at room temperature and pressure.
[0042] Unless otherwise specified, all parts or percentages are by weight.
[0043] In the present invention, all substances used are known substances and can be purchased or synthesized by known methods.
[0044] In the present invention, the devices or equipment used are all conventional devices or equipment known in the art and are commercially available.
[0045] A two-dimensional iron-nitrogen co-doped biochar sheet was synthesized in molten salt using sesame meal and trivalent iron salt solution as precursors.
[0046] Furthermore, the ferric salt is ferric chloride hexahydrate, and / or
[0047] The molten salt is a mixed salt of KCl and LiCl, and the mass ratio of KCl to LiCl is (35-75):(65-25).
[0048] A method for preparing iron-nitrogen co-doped biochar flakes, comprising the following steps:
[0049] (1) adding a certain amount of sesame meal and a certain amount of trivalent iron salt aqueous solution into a reaction vessel and mixing to obtain a mixed solution, then placing the reaction vessel in a water bath and continuously stirring at a certain temperature until the water is completely evaporated to obtain a mixture;
[0050] (2) Drying the mixture , It is then crushed into powder;
[0051] (3) grinding the powder and molten salt obtained in step (2) together until they are uniformly mixed to obtain a mixture, and then heating the mixture to a certain temperature at a certain heating rate in an inert atmosphere or a nitrogen atmosphere for a certain time to perform pyrolysis to obtain a pyrolysis product;
[0052] (4) After the furnace temperature drops to room temperature, the pyrolysis products are taken out and washed;
[0053] (5) Drying the pyrolysis product treated in step (4) to obtain iron-nitrogen co-doped biochar sheets.
[0054] Furthermore, the ferric salt in step (1) is ferric chloride hexahydrate, and / or
[0055] The mass ratio of the amount of sesame meal to the amount of the ferric salt aqueous solution in step (1) is 10:(25-50), the concentration of the ferric salt aqueous solution is 1-5 mol / L, and / or
[0056] The temperature of the water bath in step (1) is 60-90°C.
[0057] Furthermore, the molten salt is a mixed salt of KCl and LiCl, and the mass ratio of KCl to LiCl is (35-75): (65-25), and / or
[0058] The mass ratio of the powder obtained in step (2) to the molten salt is 1:(3-6).
[0059] Furthermore, the pyrolysis temperature in step (3) is 500-900°C, preferably 700-800°C, and / or
[0060] The holding time in step (3) is 1-3 hours, and / or
[0061] The heating rate in step (3) is 5-20°C / min.
[0062] Furthermore, in step (2), the mixture is dried in an oven at a temperature of 40-70° C., and / or
[0063] In step (5), the pyrolysis product is dried in an oven at a temperature of 50-80°C.
[0064] The iron-nitrogen co-doped biochar flakes are prepared by the above-mentioned preparation method.
[0065] The application of the above-mentioned iron-nitrogen co-doped biochar sheets in treating organic pollutants in oilfield produced water.
[0066] Furthermore, the steps of the application are as follows:
[0067] A certain amount of peroxymonosulfate, the iron-nitrogen co-doped biochar flakes, and an appropriate amount of water are mixed to obtain a catalytic oxidation system dominated by singlet oxygen and electron transfer, and then the catalytic oxidation system is directly added to the oilfield produced water to be treated, wherein:
[0068] The concentration of the iron-nitrogen co-doped biochar flakes in the oilfield produced water to be treated is 0.1-0.5 g / L, and the concentration of peroxymonosulfate in the oilfield produced water to be treated is 0.31-0.93 g / L.
[0069] In one embodiment, a two-dimensional iron-nitrogen co-doped biochar sheet is synthesized in molten salt using sesame meal and trivalent iron salt solution as precursors.
[0070] Furthermore, the ferric salt is ferric chloride hexahydrate, and / or
[0071] The molten salt is a mixed salt of KCl and LiCl, and the mass ratio of KCl to LiCl is 35:65.
[0072] A method for preparing iron-nitrogen co-doped biochar flakes, comprising the following steps:
[0073] (1) adding a certain amount of sesame meal and a certain amount of trivalent iron salt aqueous solution into a reaction vessel and mixing to obtain a mixed solution, then placing the reaction vessel in a water bath and continuously stirring at a certain temperature until the water is completely evaporated to obtain a mixture;
[0074] (2) Drying the mixture , It is then crushed into powder;
[0075] (3) grinding the powder and molten salt obtained in step (2) together until they are uniformly mixed to obtain a mixture, and then heating the mixture to a certain temperature at a certain heating rate in a helium atmosphere and keeping the temperature for a certain time to perform pyrolysis to obtain a pyrolysis product;
[0076] (4) After the furnace temperature drops to room temperature, the pyrolysis products are taken out and washed;
[0077] (5) Drying the pyrolysis product treated in step (4) to obtain iron-nitrogen co-doped biochar sheets.
[0078] Furthermore, the ferric salt in step (1) is ferric chloride hexahydrate, and / or
[0079] The mass ratio of the amount of sesame meal to the amount of the ferric salt aqueous solution in step (1) is 10:25, the concentration of the ferric salt aqueous solution is 1 mol / L, and / or
[0080] The temperature of the water bath in step (1) is 60°C.
[0081] Furthermore, the molten salt is a mixed salt of KCl and LiCl, and the mass ratio of KCl to LiCl is 35:65, and / or
[0082] The mass ratio of the powder obtained in step (2) to the molten salt is 1:3.
[0083] Furthermore, the pyrolysis temperature in step (3) is 500°C, and / or
[0084] The holding time in step (3) is 3 hours, and / or
[0085] The heating rate in step (3) is 5°C / min.
[0086] Furthermore, in step (2), the mixture is dried in an oven at a temperature of 40° C., and / or
[0087] In step (5), the pyrolysis product is dried in an oven at a drying temperature of 50°C.
[0088] The iron-nitrogen co-doped biochar flakes are prepared by the above-mentioned preparation method.
[0089] The application of the above-mentioned iron-nitrogen co-doped biochar sheets in treating organic pollutants in oilfield produced water.
[0090] Furthermore, the steps of the application are as follows:
[0091] A certain amount of peroxymonosulfate, the iron-nitrogen co-doped biochar flakes, and an appropriate amount of water are mixed to obtain a catalytic oxidation system dominated by singlet oxygen and electron transfer, and then the catalytic oxidation system is directly added to the oilfield produced water to be treated, wherein:
[0092] The concentration of the iron-nitrogen co-doped biochar flakes in the oilfield produced water to be treated is 0.1 g / L, and the concentration of peroxymonosulfate in the oilfield produced water to be treated is 0.31 g / L.
[0093] In another embodiment: an iron-nitrogen co-doped biochar sheet, using sesame meal and trivalent iron salt solution as precursors, and synthesizing a two-dimensional iron-nitrogen co-doped biochar sheet in molten salt.
[0094] Furthermore, the ferric salt is ferric chloride hexahydrate, and / or
[0095] The molten salt is a mixed salt of KCl and LiCl, and the mass ratio of KCl to LiCl is 75:25.
[0096] A method for preparing iron-nitrogen co-doped biochar flakes, comprising the following steps:
[0097] (1) adding a certain amount of sesame meal and a certain amount of trivalent iron salt aqueous solution into a reaction vessel and mixing to obtain a mixed solution, then placing the reaction vessel in a water bath and continuously stirring at a certain temperature until the water is completely evaporated to obtain a mixture;
[0098] (2) Drying the mixture , It is then crushed into powder;
[0099] (3) grinding the powder and molten salt obtained in step (2) together until they are uniformly mixed to obtain a mixture, and then heating the mixture to a certain temperature at a certain heating rate in a nitrogen atmosphere and keeping the temperature for a certain time to perform pyrolysis to obtain a pyrolysis product;
[0100] (4) After the furnace temperature drops to room temperature, the pyrolysis products are taken out and washed;
[0101] (5) Drying the pyrolysis product treated in step (4) to obtain iron-nitrogen co-doped biochar sheets.
[0102] Furthermore, the ferric salt in step (1) is ferric chloride hexahydrate, and / or
[0103] The mass ratio of the amount of sesame meal to the amount of the ferric salt aqueous solution in step (1) is 10:50, the concentration of the ferric salt aqueous solution is 5 mol / L, and / or
[0104] The temperature of the water bath in step (1) is 90°C.
[0105] Furthermore, the molten salt is a mixed salt of KCl and LiCl, and the mass ratio of KCl to LiCl is 75:25, and / or
[0106] The mass ratio of the powder obtained in step (2) to the molten salt is 1:6.
[0107] Furthermore, the pyrolysis temperature in step (3) is 900°C, and / or
[0108] The holding time in step (3) is 1 hour, and / or
[0109] The heating rate in step (3) is 20°C / min.
[0110] Furthermore, in step (2), the mixture is dried in an oven at a temperature of 70° C., and / or
[0111] In step (5), the pyrolysis product is dried in an oven at a drying temperature of 80°C.
[0112] The iron-nitrogen co-doped biochar flakes are prepared by the above-mentioned preparation method.
[0113] The application of the above-mentioned iron-nitrogen co-doped biochar sheets in treating organic pollutants in oilfield produced water.
[0114] Furthermore, the steps of the application are as follows:
[0115] A certain amount of peroxymonosulfate, the iron-nitrogen co-doped biochar flakes, and an appropriate amount of water are mixed to obtain a catalytic oxidation system dominated by singlet oxygen and electron transfer, and then the catalytic oxidation system is directly added to the oilfield produced water to be treated, wherein:
[0116] The concentration of the iron-nitrogen co-doped biochar flakes in the oilfield produced water to be treated is 0.5 g / L, and the concentration of peroxymonosulfate in the oilfield produced water to be treated is 0.93 g / L.
[0117] In another embodiment, a two-dimensional iron-nitrogen co-doped biochar sheet is synthesized in molten salt using sesame meal and trivalent iron salt solution as precursors.
[0118] Furthermore, the ferric salt is ferric chloride hexahydrate, and / or
[0119] The molten salt is a mixed salt of KCl and LiCl, and the mass ratio of KCl to LiCl is 55:45.
[0120] A method for preparing iron-nitrogen co-doped biochar flakes, comprising the following steps:
[0121] (1) adding a certain amount of sesame meal and a certain amount of trivalent iron salt aqueous solution into a reaction vessel and mixing to obtain a mixed solution, then placing the reaction vessel in a water bath and continuously stirring at a certain temperature until the water is completely evaporated to obtain a mixture;
[0122] (2) Drying the mixture , It is then crushed into powder;
[0123] (3) Grinding the powder and molten salt obtained in step (2) together until they are uniformly mixed to obtain a mixture, and then heating the mixture to a certain temperature at a certain heating rate in an argon atmosphere and keeping the temperature for a certain time to perform pyrolysis to obtain a pyrolysis product;
[0124] (4) After the furnace temperature drops to room temperature, the pyrolysis products are taken out and washed;
[0125] (5) Drying the pyrolysis product treated in step (4) to obtain iron-nitrogen co-doped biochar sheets.
[0126] Furthermore, the ferric salt in step (1) is ferric chloride hexahydrate, and / or
[0127] The mass ratio of the amount of sesame meal to the amount of the ferric salt aqueous solution in step (1) is 10:40, the concentration of the ferric salt aqueous solution is 4 mol / L, and / or
[0128] The temperature of the water bath in step (1) is 75°C.
[0129] Furthermore, the molten salt is a mixed salt of KCl and LiCl, and the mass ratio of KCl to LiCl is 55:45, and / or
[0130] The mass ratio of the powder obtained in step (2) to the molten salt is 1:4.
[0131] Furthermore, the pyrolysis temperature in step (3) is 800°C, and / or
[0132] The holding time in step (3) is 2 hours, and / or
[0133] The heating rate in step (3) is 10°C / min.
[0134] In another embodiment, the pyrolysis temperature in step (3) is 700° C. In another embodiment, the pyrolysis temperature in step (3) is 750° C.
[0135] Furthermore, in step (2), the mixture is dried in an oven at a temperature of 50° C., and / or
[0136] In step (5), the pyrolysis product is dried in an oven at a drying temperature of 60°C.
[0137] The iron-nitrogen co-doped biochar flakes are prepared by the above-mentioned preparation method.
[0138] The application of the above-mentioned iron-nitrogen co-doped biochar sheets in treating organic pollutants in oilfield produced water.
[0139] Furthermore, the steps of the application are as follows:
[0140] A certain amount of peroxymonosulfate, the iron-nitrogen co-doped biochar flakes, and an appropriate amount of water are mixed to obtain a catalytic oxidation system dominated by singlet oxygen and electron transfer, and then the catalytic oxidation system is directly added to the oilfield produced water to be treated, wherein:
[0141] The concentration of the iron-nitrogen co-doped biochar flakes in the oilfield produced water to be treated is 0.3 g / L, and the concentration of peroxymonosulfate in the oilfield produced water to be treated is 0.62 g / L.
[0142] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.
[0143] Example 1
[0144] A method for preparing iron-nitrogen co-doped biochar flakes, comprising the following steps:
[0145] (1) 10 g of sesame meal was mixed with 50 g of ferric chloride hexahydrate aqueous solution to obtain a mixed solution, and then the mixed solution was placed in a 90° C. water bath and continuously stirred until the water was completely evaporated to obtain a mixture;
[0146] (2) Place the evaporated solid in an oven and bake it at 60°C until it is completely dry, then crush it into powder;
[0147] (3) Accurately weigh 10 g of the powder obtained in step (2), mix it with 30 g of a mixed salt of KCl and LiCl (the mass ratio of KCl to LiCl is 55:45), and grind it evenly. Then, place the obtained mixture in a tube furnace, heat it to 800° C. at a heating rate of 10° C. / min under a nitrogen atmosphere, and maintain it for two hours for pyrolysis to obtain a pyrolysis product;
[0148] (4) After the furnace temperature drops to room temperature, the pyrolysis product is taken out of the tube furnace, and is repeatedly filtered and washed to completely remove the salt in the pyrolysis product;
[0149] (5) The pyrolysis product treated in step (4) is placed in an oven and dried at a temperature of 60° C. until completely dry, thereby obtaining iron-nitrogen co-doped biochar flakes, referred to as FSBC-800.
[0150] Example 2
[0151] The method is substantially the same as Example 1, except that the pyrolysis temperature in step (3) is 500° C., and the obtained iron-nitrogen co-doped biochar flakes are referred to as FSBC-500.
[0152] Example 3
[0153] The method is similar to Example 1, except that the pyrolysis temperature in step (3) is 600° C., and the obtained iron-nitrogen co-doped biochar flakes are referred to as FSBC-600.
[0154] Example 4
[0155] The method is substantially the same as Example 1, except that the pyrolysis temperature in step (3) is 700° C., and the obtained iron-nitrogen co-doped biochar flakes are referred to as FSBC-700.
[0156] Example 5
[0157] The method is substantially the same as Example 1, except that the pyrolysis temperature in step (3) is 900° C., and the obtained iron-nitrogen co-doped biochar flakes are referred to as FSBC-900.
[0158] Comparative Example 1
[0159] (1) Accurately weigh 10 g of biochar powder, mix it with 30 g of a mixed salt of KCl and LiCl (the mass ratio of KCl to LiCl is 55:45), and grind it evenly. Then, place the obtained mixture in a tube furnace, heat it to 800 °C at a heating rate of 10 °C / min under a nitrogen atmosphere, and keep it for two hours for pyrolysis to obtain a pyrolysis product;
[0160] (2) After the furnace temperature drops to room temperature, the pyrolysis product is taken out of the tube furnace, and is repeatedly filtered and washed to completely remove the salt in the pyrolysis product;
[0161] (3) The pyrolysis product treated in step (2) is placed in an oven and dried at a temperature of 60° C. until completely dry, thereby obtaining biochar, referred to as SBC-800.
[0162] Comparative Example 2
[0163] Original biochar, named BC-800.
[0164] Performance characterization:
[0165] 1. SEM
[0166] The iron-nitrogen co-doped biochar flakes FSBC-800, biochar SBC-800 and original biochar BC-800 obtained in Example 1 were subjected to SEM examination. The specific results are shown in Figure 1a-Figure 1c .from Figure 1c It can be seen that the iron-nitrogen co-doped biochar flakes FSBC-800 obtained in Example 1 have a two-dimensional flake morphology at the microscopic level.
[0167] 2. XRD
[0168] XRD tests were performed on the iron-nitrogen co-doped biochar sheets obtained in Examples 1-5 and Comparative Examples 1-2, and the results are shown in Table 1. Figure 2a and Figure 2b . Figure 2a and Figure 2b It mainly explains the phase composition of the iron-nitrogen co-doped biochar flakes prepared by the present invention.
[0169] 3. Raman spectroscopy
[0170] Raman spectroscopy was performed on the iron-nitrogen co-doped biochar sheets obtained in Examples 1-5 and Comparative Examples 1-2, and the results are shown in Table 1. Figure 3a and Figure 3b .from Figure 3a and Figure 3b It can be seen that the iron-nitrogen co-doped biochar flakes prepared by the present invention have a higher degree of defect (ID / IG) than the original biochar, breaking through the inert conjugated framework of the original biochar.
[0171] 4. FTIR
[0172] FTIR detection was performed on the iron-nitrogen co-doped biochar sheets obtained in Examples 1-5 and Comparative Examples 1-2, and the results are shown in Table 1. Figure 4a and Figure 4b . Figure 4a and Figure 4b The surface chemical properties of the iron-nitrogen co-doped biochar flakes provided by the present invention, such as surface chemical groups and surface defects, are described.
[0173] 5. Activation effect on peroxymonosulfate
[0174] For the same peroxymonosulfate, the iron-nitrogen co-doped biochar sheets obtained in Examples 1-5 and Comparative Examples 1-2 were activated, and the results were as follows: Figure 5 As shown, from Figure 5 It can be seen that under the same process conditions, the catalyst synthesized at a pyrolysis temperature of 800°C has the best activation effect on peroxymonosulfate.
[0175] 6. Catalytic degradation of tetracycline in water by a catalytic oxidation system consisting of iron-nitrogen co-doped biochar sheets and peroxymonosulfate:
[0176] 6.1 Model pollutant used: 10 mg / L tetracycline hydrochloride, volume 100 mL.
[0177] 6.2 Weigh a certain amount of the iron-nitrogen co-doped biochar flakes FSBC-800 prepared in Example 1 and a corresponding amount of permonosulfate. Mix the iron-nitrogen co-doped biochar flakes FSBC-800 and permonosulfate and add them to the tetracycline hydrochloride solution. Stir at 350 rpm to initiate the catalytic reaction. At 0, 1, 2, 4, 6, 8, and 10 minutes after the start of the reaction, 2 mL of water samples were syringed in and quenched with 2 mL of saturated sodium thiosulfate. The remaining tetracycline concentration was immediately analyzed using a UV spectrophotometer.
[0178] 6.3 Comparison of the catalytic performance of peroxymonosulfate with that of the original biochar The following method was adopted: 0.04 g of FSBC-800 (biochar provided by the present invention) and BC-800 (original biochar) and 0.0614 g of peroxymonosulfate were weighed and added to 100 mL of 10 mg / L tetracycline solution to start the experiment. The experimental results are shown in FIG. Figure 6 As shown in the figure, compared with the original biochar BC-800, the modification method of iron-nitrogen co-doped biochar flakes FSBC-800 enables the biochar to break through the limitations of the inert conjugated carbon framework and greatly improve the activation performance of peroxymonosulfate.
[0179] 6.4 The degradation effect of the catalytic oxidation system composed of iron-nitrogen co-doped biochar sheets and peroxymonosulfate at different catalyst concentrations on tetracycline was tested by the following method: 0.01g, 0.02g, 0.03g, 0.04g, and 0.05g of iron-nitrogen co-doped biochar sheets FSBC-800 and 0.0614g of peroxymonosulfate were weighed and added to 100mL of 10mg / L tetracycline solution to start the experiment. The experimental results are shown in Figure 6. Figure 7 As shown, from Figure 7 It can be seen that the catalytic oxidation system has an excellent degradation effect on tetracycline at a FSBC-800 concentration of 0.4 g / L.
[0180] 6.5 Degradation effect of tetracycline by catalytic oxidation system composed of iron-nitrogen co-doped biochar sheets and permonosulfate at different permonosulfate concentrations The following method was adopted: 0.0154g, 0.0310g, 0.0462g, 0.0614g and 0.07675g of permonosulfate and 0.04g of FSBC-800 were weighed and added to 100mL of 10mg / L tetracycline solution to start the experiment. The experimental results are shown in Figure 2. Figure 8 As shown, it can be seen that the catalytic oxidation system composed of 0.614 g / L iron and nitrogen co-doped biochar sheets and peroxymonosulfate has an excellent degradation effect on tetracycline.
[0181] 6.6 The degradation effect of tetracycline by the catalytic oxidation system composed of singlet oxygen-dominated iron-nitrogen co-doped biochar sheets and peroxymonosulfate in the presence of different anions was tested by the following method: 100 mL of a 10 mg / L tetracycline solution containing chloride, carbonate, bicarbonate, sulfate, dihydrogen phosphate, and nitrate ions at concentrations of 2 m, 10 mM, 20 mM, 50 mM, and 250 mM was prepared, and 0.0614 g of peroxymonosulfate and 0.04 g of FSBC-800 were weighed and added to the above solution for the experiment. The experimental results are shown in Figure 6. Figure 9a-9fAs shown, it can be seen that the effects of chloride, carbonate, bicarbonate, sulfate, dihydrogen phosphate, and nitrate ions on the degradation of tetracycline in the system are very weak.
[0182] 6.7 The quenching effect of ethanol, tert-butanol, furfuryl alcohol, chloroform and dimethyl sulfoxide on the catalytic oxidation system composed of iron and nitrogen co-doped biochar sheets FSBC-800 and peroxymonosulfate was tested by the following method: 100 mL of 10 mg / L tetracycline solution containing different concentrations of ethanol, tert-butanol and furfuryl alcohol was prepared, and 0.0614 g of peroxymonosulfate and 0.04 g of FSBC-800 were added to the above solution for the experiment. The experimental results are shown in Figure 6. Figure 10 As shown, it can be seen that, except for furfuryl alcohol, the quenching effect of the other quenchers on the catalytic oxidation system is very weak, while the quenching effect of furfuryl alcohol on the catalytic oxidation system is very strong, proving that the active oxygen in the system is mainly singlet oxygen.
[0183] LSV, it and open circuit voltage curves of iron-nitrogen co-doped biochar sheets FSBC-800, such as Figure 11a-Figure 11c As shown, it is proved that the activation pathway of peroxymonosulfate by iron-nitrogen co-doped biochar sheets FSBC-800 includes an electron transfer pathway.
[0184] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.
Claims
1. An iron-nitrogen co-doped biochar sheet, characterized in that: Two-dimensional iron-nitrogen co-doped biochar sheets were synthesized in molten salt using sesame meal and trivalent iron salt solution as precursors.
2. The iron-nitrogen co-doped biochar sheet according to claim 1, characterized in that: The ferric salt is ferric chloride hexahydrate, and / or The molten salt is a mixed salt of KCl and LiCl, and the mass ratio of KCl to LiCl is (35-75):(65-25).
3. A method for preparing iron-nitrogen co-doped biochar flakes, characterized in that: Here are the steps: (1) adding a certain amount of sesame meal and a certain amount of trivalent iron salt aqueous solution into a reaction vessel and mixing to obtain a mixed solution, then placing the reaction vessel in a water bath and continuously stirring at a certain temperature until the water is completely evaporated to obtain a mixture; (2) Drying the mixture , It is then crushed into powder; (3) grinding the powder and molten salt obtained in step (2) together until they are uniformly mixed to obtain a mixture, and then heating the mixture to a certain temperature at a certain heating rate in an inert atmosphere or a nitrogen atmosphere for a certain time to perform pyrolysis to obtain a pyrolysis product; (4) After the furnace temperature drops to room temperature, the pyrolysis products are taken out and washed; (5) Drying the pyrolysis product treated in step (4) to obtain iron-nitrogen co-doped biochar sheets.
4. The method for preparing an iron-nitrogen co-doped biochar sheet according to claim 3, wherein: The ferric salt in step (1) is ferric chloride hexahydrate, and / or The mass ratio of the amount of sesame meal to the amount of the ferric salt aqueous solution in step (1) is 10:(25-50), the concentration of the ferric salt aqueous solution is 1-5 mol / L, and / or The temperature of the water bath in step (1) is 60-90°C.
5. The method for preparing an iron-nitrogen co-doped biochar sheet according to claim 3, wherein: The molten salt is a mixed salt of KCl and LiCl, and the mass ratio of KCl to LiCl is (35-75): (65-25), and / or The mass ratio of the powder obtained in step (2) to the molten salt is 1:(3-6).
6. The method for preparing an iron-nitrogen co-doped biochar sheet according to claim 3, wherein: The pyrolysis temperature in step (3) is 500-900°C, preferably 700-800°C, and / or The holding time in step (3) is 1-3 hours, and / or The heating rate in step (3) is 5-20°C / min.
7. The method for preparing an iron-nitrogen co-doped biochar sheet according to claim 3, wherein: In step (2), the mixture is dried in an oven at a temperature of 40-70°C, and / or In step (5), the pyrolysis product is dried in an oven at a temperature of 50-80°C.
8. Iron-nitrogen co-doped biochar flakes, characterized in that: It is prepared by the preparation method according to any one of claims 3 to 7.
9. Use of the iron-nitrogen co-doped biochar sheet according to claim 8 in treating organic pollutants in oilfield produced water.
10. The use according to claim 9, characterized in that The steps of the application are as follows: A certain amount of peroxymonosulfate, the iron-nitrogen co-doped biochar flakes, and an appropriate amount of water are mixed to obtain a catalytic oxidation system dominated by singlet oxygen and electron transfer, and then the catalytic oxidation system is directly added to the oilfield produced water to be treated, wherein: The concentration of the iron-nitrogen co-doped biochar flakes in the oilfield produced water to be treated is 0.1-0.5 g / L, and the concentration of peroxymonosulfate in the oilfield produced water to be treated is 0.31-0.93 g / L.
Citation Information
Patent Citations
Water treatment method for removing pollutants through secondary iron mineral activation and peroxymonosulfate oxidation
CN107055744A
Method for removing organic pollutants in water by photo-assisted activation of peroxymonosulfate
CN114229949A
Method for improving electron utilization rate of nano zero-valent iron during reduction purification of selenite and selenate in water body
CN115259336A